2005
DOI: 10.1111/j.1467-7687.2005.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of spatial parallel coding in children's drawing

Abstract: When drawing real scenes or copying simple geometric figures young children are highly sensitive to parallel cues and use them effectively. However, this sensitivity can break down in surprisingly simple tasks such as copying a single line where robust directional errors occur despite the presence of parallel cues. Before we can conclude that this directional bias is a limiting case it needs to be shown that any given parallel cues are indeed being processed. We achieved this by using a texture-defined contour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…J0313+413: the large‐scale structure of this broad line radio galaxy (Marchã et al 1996) was presented by de Bruyn (1989) with rather coarse resolution. Subsequent published observations with the VLA and VLBI have revealed a prominent core and a weak jet‐like extension (Patnaik et al 1992; Henstock et al 1995; Taylor et al 1996; Schoenmakers et al 2000a; Fey & Charlot 2000).…”
Section: Observational Resultsmentioning
confidence: 99%
“…J0313+413: the large‐scale structure of this broad line radio galaxy (Marchã et al 1996) was presented by de Bruyn (1989) with rather coarse resolution. Subsequent published observations with the VLA and VLBI have revealed a prominent core and a weak jet‐like extension (Patnaik et al 1992; Henstock et al 1995; Taylor et al 1996; Schoenmakers et al 2000a; Fey & Charlot 2000).…”
Section: Observational Resultsmentioning
confidence: 99%
“…This source was already studied by Hocuk & Barthel (2010), that estimated a viewing angle of 57 degrees, and a core variability up to 25% in ten years. Another two sources, B3 0309+411B and 4C 74.26, are known to have a variable core flux density from previous works: the first was presented by Saikia et al (1984) andde Bruyn (1989), who show an inverted spectrum up to 100 GHz with a variable core flux density, while the latter was investigated by Riley et al (1989), Pearson et al (1992), and Konar et al (2004), who found a variability of ∼50% at 5 GHz over 14 years.…”
Section: Variabilitymentioning
confidence: 99%
“…QSO B0241+62 and IGR J13109−5552) are well‐known BLRG [see Table 1 and NASA/IPAC Extragalactic Database (NED); Ballantyne 2005 and Molina et al 2007] and show a morphology with two lobes extending from the central nucleus [see e.g. NRAO/VLA Sky Survey (NVSS) contour maps available in NED]; the extension of the lobes for B3 0309+411 and 4C 74.26 is more than 1 Mpc, hence their classification as giant radio galaxies (Riley et al 1988; de Bruyn 1989). These double‐lobed objects are classified in the literature as FR II galaxies, with the exception of 4C 74.26 and S5 2116+81, which still have an uncertain/unknown nature.…”
Section: The Samplementioning
confidence: 99%